Systematic Literature Review: PBL Model Assisted by PhET Simulation to Improve Students' Critical Thinking Ability - Qothrunnada, Qothrunnada; Rokhmat, Joni (Contextual Natural Science Education Journal, 2024)
This study was conducted to demonstrate the effectiveness of implementing a problem-based learning model in enhancing students' critical thinking skills at the high school level or its equivalent. The type of research carried out was a systematic literature review, following seven stages: formulating research questions, establishing selection criteria, developing search strategies, selecting studies based on selection criteria, assessing research quality, synthesizing results for the research questions, and reporting findings.Article searches were conducted using Google Scholar, SINTA, and ProQuest, with the assistance of the Publish or Perish application, utilizing keywords such as "critical thinking skills," "problem-based learning," and "physics." A total of 35 articles were obtained from the study, of which 33 met the inclusion criteria. The quality assessment results indicated that the identified articles were of good quality and were published in SINTA and SCOPUS. The implementation of problem-based learning can be integrated with other media, such as PhET simulations, websites, and Microsoft Teams, to enhance students' critical thinking skills. The review of these articles confirms that the overall application of the problem-based learning model can effectively improve students' critical thinking skills in physics.